An Analysis of Sociopathic Attributes of Sherlock Holmes In A Study in Scarlet - Muhammad Dzaky Murtadha (Passage, 2019)
Sherlock Holmes is a prominent fictional character in detective fiction that has inspired many literary works. However, there are debates nowadays concerning whether or not Holmes is categorized as a sociopath, and the present study was done to find the answer. The present study aims to investigate the extent to which sociopathic characteristics are attributed to Sherlock Holmes in A Study in Scarlet (2013). The data used in the study comes mainly from the narration of Dr. Watson concerning the behaviors of Sherlock Holmes. The theories applied in the data analysis are Genette’s Focalization (1980), Minderop’s Characterization (2005), Hare’s Psychopathy Checklist-Revised (PCL-R) (1998), and Scarlet’s (2011) categorization of Hare’s PCL-R items. The study reveals that the sociopathic attributes are constructed through the assumption of Dr. Watson and Stamford. The findings also show that the score of Hare’s (1998) PCL-R of Holmes is eleven, which is lower than the minimum score of a sociopath (22-29) and higher than a normal person (0-6), thus he cannot be classified as both. For this reason, further studies concerning the topic are needed to identify the suitable category of Sherlock Holmes. Keywords: characterization, focalization, Hare’s psychopathy checklist-revised, Sherlock Holmes, sociopathic attributes